Switching from an Inclining to a Zero-Level Unemployment Benefit Profile: Good for Work Incentives? - Bart Cockx; Koen Declercq; Muriel Dejemeppe; Leda Inga; Bruno Van der Linden (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper evaluates the impact on the transition to work of a policy reform in Belgium that restricted the access to a specific unemployment insurance scheme for young labor market entrants. This scheme entitles youths with no or little labor market experience to unemployment benefits after a waiting period of one year. As of 2015, the Belgian government unexpectedly scrapped benefit eligibility for youths who start the waiting period at the age of 24 or older. The reform implied a change from an inclining to a flat rate (zero-level) benefit profile. We use a difference-in-differences approach to identify the causal impact of this reform on fresh university graduates. Our main finding is that this reform only increases the transition to very short-lived jobs.
Keywords: J64; J65; J68; 330; youth unemployment; unemployment insurance; policy evaluation; difference-in-differences